Complete mitochondrial genome sequence of Emberiza sulphurata (Emberizidae: Emberiza). Issue 1 (1st January 2017) - Lee, Mu-Yeong; Jeon, Hey Sook; An, Junghwa
Abstract: The Japanese yellow bunting ( Emberiza sulphurata ) is considered to be an endangered species. Here, the complete mitochondrial genome of E. sulphurata (16, 797 bp in length) was determined. The genome consists of 37 genes (13 protein-coding genes, two ribosomal RNA genes, and 22 transfer RNA genes) and one control region (D-loop), and so is highly similar in architecture to the typical vertebrate mtDNA genome. The base composition of the mtDNA was A (29.9%), C (32.6%), G (14.5%), and T (23.0%), so the percentage of A and T (52.9%) was slightly higher than that of G and C. All the genes in E. sulphurata were encoded on the H-strand, except for the genes for the ND6 subunit and eight tRNAs, which were encoded on the L-stand. Phylogenetic analysis using Emberizidae mitogenomes revealed that E. sulphurata was grouped into the family Emberizidae and that E. spodocephala is the most closely related species.